Dampak E-Service Quality dan Electronic Word of Mouth (eWOM) terhadap Minat Beli Gojek Plus di Jakarta - Faisal Chandra Ramadhan; Sagita, Ardio (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the individual and combined effects of e-service quality and electronic word-of-mouth on purchase intention for Gojek Plus subscriptions among 385 users in Jakarta. Using a quantitative causal design, data were collected through an online survey with purposive sampling and analyzed using multiple linear regression in SPSS. The findings show that e-service quality and electronic word-of-mouth each have a positive and significant effect on purchase intention, jointly explaining 46.7% of its variance. These results suggest that digital platforms should improve service efficiency, data privacy, and positive electronic word-of-mouth to strengthen subscription adoption. Keywords: E-service Quality; eWOM; Purchase Intention; Subscription Economy; Gojek Plus